Correlation between heparanase gene polymorphism and susceptibility to endometrial cancer - Hanyu Cao; Shuo Yang; Xiuzhang Yu; Mingrong Xi (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Endometrial cancer is one of the three most common malignancies in the female genital tract. Previous studies have demonstrated the association between heparanase (HPSE, OMIM 604,724) single‐nucleotide polymorphism (SNP) and cancer risk in several cancers. However, its role in endometrial cancer remains unclear. The present study investigated the effects of HPSE SNPs on the susceptibility and clinicopathological parameters in patients with endometrial cancer. Methods HPSE SNPs of rs4693608 (G > A) and rs4364254 (C > T) were analyzed using polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) assay in 270 endometrial cancer patients and 320 healthy controls. Results The investigation indicated that the HPSE SNP rs4693608 with GG showed a protective effect from EC in both codominant (adjusted OR = 0.41, 95%CI = 0.21–0.81, p = .026) and recessive models (adjusted OR = 0.43, 95%CI = 0.22–0.82, p = .0076). No significant differences were found in the incidences of EC patients with the rs4364254 polymorphisms compared to controls. Moreover, a significantly increased distribution of A/A (rs4693608) was observed in patients with grade ≥ 2 (p = .03) and in patients with positive cervical invasion (p = .042) while patients with T/C (rs4364254) had lower tumor grade. Conclusion Our study suggested that HPSE SNP of rs4693608 correlated strongly with susceptibility to EC, and HPSE SNPs might be a potential biomarker for prognosis of endometrial cancer.